Investigation of PC cluster productivity in quantum mechanical molecular computations - Egidijus Pankevičius; Rimantas-Jonas Rakauskas; Juozas Šulskus; Svajonė Vošterienė (Lietuvos Matematikos Rinkinys)
There is not abstract.